ANNUAL REPORT OF THE CENTRAL INLAND FISHERIES RESEARCH INSTITUTE, BARRACKPORE FOR THE YEAR 1960-61 - Barrackpore, Central Inland Fisheries Research Instit (Indian Journal of Fisheries, 2011)
Substantial progress was achieved during the year in all investigations undertaken by the Research Institute. There was also an all-round expansion of activities of the various sections and units, under both normal and Second Five-Year Plan programmes. During the year under report, 6 additional residential quarters were constructed at Barrackpore at a cost of Rs. 1,22,200. An area of 35-25 acres of land was acquired for the establishment of an experimental fish farm in Kakdwip. The construction of Garage, Workshop and Stores at Headquarters was sanctioned at an estimated cost of Rs. 1,31,000. Sanction for the construction of an aquarium at a cost of Rs. 99,615 has also been received from the Government. ’ The draft proposals for the implementation of the Third Five-Year Plan programme were submitted to Government. The following Officers were appointed